Speech Acts in Hailey Bieber's "Motherhood Journey" Interview: A Searlean Perspective - Aulia, Dinda Annisa'; Rosyidah, Yaqutatul Yumna Nur; Daulay, Irma Khoirot (Journal of English Language and Education, 2026)
This study investigates the speech acts in Hayle Bieber’s motherhood journey interview with WSJ.Style using Searle’s framework (1979), containing an illocutionary point, direction of fit, and psychological state. Employing qualitative content analysis, 34 units of utterances were identified. The discoverers emphasize that assertive (58,82%) dominates the result, followed by expressive (38,24%) in the second position. This determines that Hailey Bieber interviewed to share her experiences and express emotions as a new mom. In a case of direction of fit, most utterances are identified as word-to-world, portraying her tendency to describe events that correspond to reality. Hence, null fit emerges in expressive utterances to cover her personal emotions. Otherwise, psychological state represents belief and emotions, which are proven based on her statements on personal conviction and affective responses. Certainly, the findings expose that Hailey Bieber builds an identity as a reflective and emotionally attached mother. Furthermore, this study verifies how speech acts determine personal branding in celebrities’ media interviews and contributes to a deeper understanding of language use attached to emotions.